Retinopathy of prematurity – developing too soon in babies born too early : A report of three cases - Obajolowo Tokunbo Sarah; Olokoba Lateefat Bukola; Olatunji Victoria Ayodeji; Ademola-Popoola Dupe Serifat; Adesiyun Omotayo Olukemi; Mokuolu Oluwabunmi Shade (Nigerian Journal of Paediatrics, 2024)
Nigeria has the third largest incidence of premature birth, after India and China. Most babies that will require treatment for retinopathy of prematurity (ROP) have birth weight (BW) less than 1500g and gestational age (GA) less than 32 weeks, with initial eye examination within the first 30 days of life. This report aims to present the findings in three babies with vision threatening ROP that developed at less than 30 days of life. Routine screening for ROP was conducted for three babies. One was born GA 33 weeks, BW 1.6kg, screened for ROP on the 13th day of life, while the other two were a set of twins born at GA of 33 weeks, both BW 1.3kg, screened for ROP first on the 16th day of life. The twins were found CC –BY 4.0 to have arborizing vessels at the initial exam, which progressed to stage 3 pre-plus ROP by the 23rd day of life. The 3rd child had stage -3 plus disease at the first screening, warranting immediate LASER therapy. The screening criteria of Nigeria ROP group is BW ≤ 1500g or GA of ≤ 34 weeks, with the first eye examination within the first 30 days of life. These case reports show that larger babies can also develop sight threatening ROP within the first two weeks of life. There is a need for constant review of ROP screening criteria and timing based on locally available data